Does Hypertension Remain after Kidney Transplantation? - Gholamreza Pourmand; Sanaz Dehghani; Mohamad Reza Rahmati; Abdolrasoul Mehrsai; Shahram Gooran; Farimah Alizadeh; Siavash Khaki; Seyede Hamideh Mortazavi; Naghmeh Pourmand (Acta Medica Iranica, 2015)
Hypertension is a common complication of kidney transplantation with the prevalence of 80%. Studies in adults have shown a high prevalence of hypertension (HTN) in the first three months of transplantation while this rate is reduced to 50- 60% at the end of the first year. HTN remains as a major risk factor for cardiovascular diseases, lower graft survival rates and poor function of transplanted kidney in adults and children. In this retrospective study, medical records of 400 kidney transplantation patients of Sina Hospital were evaluated. Patients were followed monthly for the 1st year, every two months in the 2nd year and every three months after that. In this study 244 (61%) patients were male. Mean ± SD age of recipients was 39.3 ± 13.8 years. In most patients (40.8%) the cause of end-stage renal disease (ESRD) was unknown followed by HTN (26.3%). A total of 166 (41.5%) patients had been hypertensive before transplantation and 234 (58.5%) had normal blood pressure. Among these 234 individuals, 94 (40.2%) developed post-transplantation HTN. On the other hand, among 166 pre-transplant hypertensive patients, 86 patients (56.8%) remained hypertensive after transplantation. Totally 180 (45%) patients had post-transplantation HTN and 220 patients (55%) didn't develop HTN. Based on the findings, the incidence of post-transplantation hypertension is high, and kidney transplantation does not lead to remission of hypertension. On the other hand, hypertension is one of the main causes of ESRD. Thus, early screening of hypertension can prevent kidney damage and reduce further problems in renal transplant recipients.